Dedução transcendental e norma fundamental: questões de legitimação em Kant e Kelsen - Genro, Guilherme Saideles (2007)
This thesis intends to analyse the notions of transcendental deduction and basic norm, presented in the works of Kant and Kelsen, respectively. These concepts are used by the authors quoted as a form to legitimize the objective validity of knowledge, in a general sense in Kant, and specifically the knowledge of Law in Kelsen. The idea to carry out this comparison originated from the analogy used by Kelsen, in his book Pure Theory of Law, between the Kantian categories of understanding, justified through of the transcendental deduction in the Critique of Pure Reason, and the basic norm, where the two notions appear like conditions of the possibility of knowledge. The work is divided into two chapters that deal, respectively, of the transcendental deduction, Objectives, strategies and method of the transcendental deduction of the categories , and of the basic norm, The legal thought of Kelsen and the Kantian s inspiration of the basic norm . Each of them will try to present the assumptions and characteristics of the concepts in question, starting from the objectives that led Kant and Kelsen to formulate them as forms of legitimation of knowledge. Finally, a comparison between the two projects and a discussion about the possibility of a transcendental deduction of the basic norm will be expounded, as well as some conclusions that can be drawn from the work